1989
DOI: 10.1002/bjs.1800760906
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing local recurrence after excision and radiotherapy for primary breast cancer

Abstract: Between November 1979 and December 1986, 263 patients were treated for primary breast cancer by local excision and radiotherapy at the City Hospital, Nottingham. Local recurrence within the treated breast occurred in 56 patients (21 per cent), in 18 (6.8 per cent) of whom it was gross and uncontrollable. An analysis of clinicopathological features shows patient age, nodal status, tumour size, presence of definitive vascular invasion, adjacent ductal carcinoma in situ and grade to be predictive of local recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(46 citation statements)
references
References 17 publications
3
42
0
1
Order By: Relevance
“…It has been supported by many previous studies. [7][8][9][10][11] Jobsen et al reported that age Ͻ 40 years was the only significant predictor of IBTR for women treated with BCT with pathologic T1 tumors and negative lymph node status. 10 Harrold et al showed a correlation with young age and IBTR by using a cutpoint age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been supported by many previous studies. [7][8][9][10][11] Jobsen et al reported that age Ͻ 40 years was the only significant predictor of IBTR for women treated with BCT with pathologic T1 tumors and negative lymph node status. 10 Harrold et al showed a correlation with young age and IBTR by using a cutpoint age of 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young women were generally thought to have a higher frequency of local recurrence. [7][8][9][10][11] Kroman et al recently reported a relation between young age and increasing risk of IBTR, from a study of BCT with over 2000 patients. 12 The European Organization for Research and Treatment of Cancer (EORTC) trial also confirmed the impact of age.…”
mentioning
confidence: 99%
“…The step-wise log-normal model included tumor size and lymph node status which are clinically useful 23 components of pathological staging, along with histological type. Nuclear grade 24,25 and LVPI 26,27 are also recognized as important prognostic factors. Interestingly, this study did not find that over expression of the Her 2 neu oncogene was related to a poorer prognosis, as was found in a previous study of node-negative patients; 28…”
Section: Figmentioning
confidence: 99%
“…Local recurrence after breast-conserving surgery and radiotherapy is said to occur in around 8% of cases by 5 years (10), although much higher recurrence rates have been reported (23). The majority of surgeons (69%) participating in this study would perform a mastectomy for local recurrence, with only 6% performing a further excision of the recurrence.…”
Section: Discussionmentioning
confidence: 97%